2002
DOI: 10.1159/000066176
|View full text |Cite
|
Sign up to set email alerts
|

Management and Results of Retinal Detachment after Silicone Oil Removal

Abstract: Of the 168 eyes undergoing silicone oil removal from 1993 to 2000, 34 developed retinal detachment after the removal of silicone oil. The management and the results of the 34 eyes were reviewed. Surgical procedures included pars plana vitrectomy, encircling band, cryocoagulation, endotamponade. Five of the 34 eyes had a second retinal detachment after these operations. One of these 5 eyes had a third retinal detachment. Final retinal reattachment was achieved in all eyes. Visual acuity decreased in 16 of the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…In general, the functional outcome after repeated retinal detachment surgery is considered poor [16] even in cases that have successful anatomical result. In the present study, we evaluated the functional outcome of the anatomically successful cases choosing a relatively high cut-off value of final visual acuity compared to the majority of relevant studies (0.30logMAR or 20/40 in the Snellen chart) [6, 7, 14, 16, 17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the functional outcome after repeated retinal detachment surgery is considered poor [16] even in cases that have successful anatomical result. In the present study, we evaluated the functional outcome of the anatomically successful cases choosing a relatively high cut-off value of final visual acuity compared to the majority of relevant studies (0.30logMAR or 20/40 in the Snellen chart) [6, 7, 14, 16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we evaluated the functional outcome of the anatomically successful cases choosing a relatively high cut-off value of final visual acuity compared to the majority of relevant studies (0.30logMAR or 20/40 in the Snellen chart) [6, 7, 14, 16, 17]. Even with this high cut-off value we were able to show that even after multiple recurrences and operations, the retina is capable of retaining quite good functionality if it is finally maintained attached.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence is widely variable: most studies have reported an incidence of 20–25%,1 6 8 9 11 some 15–20%,4 10 and a few below 10% 2 5 13. Several mechanisms have been advocated for redetachment: reopening of pre-existing breaks, posterior migration of an occult RD or new retinal break formation,6 and residual vitreoretinal traction at the vitreous base 13.…”
Section: Discussionmentioning
confidence: 99%
“…Most adverse effects such as hypotony, raised IOP and bullous or band keratopathy are well-known complications of standard silicone oil and do not differ clinically significantly in number and severity [1,16,18,19] . Despite the fact that the good intraocular tolerance of Densiron 68 recently described by Wong et al [13] could be confirmed in this study by the comparison of the number of adverse effects with standard versus heavy silicone oil in vitreous in most cases, the tendency towards a more frequent moderate intraocular inflammation with Densiron 68 in situ should be carefully observed in future studies.…”
Section: Discussionmentioning
confidence: 99%